Consumer Behavior in Islamic Perspective - Othman, Hilmi; Yahya, Mohd Azam Bin; Wahab, Noor Jeffri Abdul (Modern Perspectives in Economics, Business and Management Vol. 4, 2021)
Islam has provided guidance to the human world in consumer behaviour. The only reliable source for Muslims is the al-Quran and the Sunnah which are guidelines for life. Consumer Behaviour is principles outlined in Islam as a guide to act in ways that are not consistent with specified sharia. Behaviour in Islam does not only focus on human relations. The Buy Muslim First (BMF) campaign is encourages Muslim buyers to prioritize the purchase of Muslim products, where Muslim traders will issue zakat and thereby develop the social economy of Muslims. This research is a quantitative study using descriptive and inferential approaches. The main objective of this research is to analyze the impact of BMF campaign on the purchasing behavior of young Muslims behaviors. Using the Muslim consumer behavior model Based on 100 respondents representing the young group was selected to answer the questionnaire using the Likert scale method. Data from the questionnaire were analyzed using SPSS Multiple Regression tests, the result of F test is 6.595> value F. then the main findings of this study explain that there is the influence of BMF campaign on young Muslim users is 21.7% (based on R Square value). Four main aspects influence the behavior of young buyers are Intention, Expenses, Religious Brotherhood and power in purchasing. All these aspects will have a direct impact on Muslim traders, it is hoped that there will be a continuation study to study these four aspects that have a significant impact on the behavior of Muslim consumers.